Education 4.0 Maturity Models for Society 5.0: Systematic literature review - González-Pérez Laura Icela; Ramírez-Montoya María Soledad; Enciso-Gonzalez Juan Antonio (Cogent Business & Management, 2023)
Society 5.0 is a transformative vision for the future driven by integrating digital technologies and human-centered approaches, fusing with cyber-physical spaces to create a smart society that addresses megatrends through innovative and collaborative solutions by stakeholders. This article analyzes Maturity Models (MMs) in Higher Education to identify the components of Education 4.0 that aim to achieve Society 5.0, seeking the dimensions and levels associated with the quintuple helix and the mission of the HEIs. We conducted a systematic literature review (SLR) guided by research questions to highlight studies that address Maturity Models worldwide, identify components of Education 4.0 in the MM, research methods and instruments used, internal and external stakeholders, and some characteristics of the university missions. The study method employed was a Systematic Review analyzing 26 articles from 2018 to 2023 found in WoS and Scopus databases using inclusion and exclusion criteria under a Prisma workflow. The findings were that the HEIs must: a) analyze dimensions of various Education 4.0 components in a balanced way, b) incorporate comparative designs and mixed methods of the MM models, c) provide technology transfer services, training, and data centers, d) provide fully open environments to educate all citizens inclusively, and e) use sustainable MMs for a significant difference in impact. This review offers educational leaders and policymakers the methodologies for measuring the Education 4.0 path to Society 5.0.
Keywords: 650; competencies; Education 4.0; educational innovation; higher education; maturity model; Society 5.0